Propulsion of blood through the right heart circulatory system. (2nd January 2018) - Næsheim, Torvind; How, Ole-Jakob; Myrmel, Truls
Abstract: Venous return, the right heart function and the pulmonary circulation is an integrated functional unit. The right ventricle is particularly load sensitive, and will be influenced directly by the venous and pulmonary physiology. In this paper we present important physiological principles that govern the diagnosis and treatment of dysfunctions affecting the return of blood to the heart and the transfer of the cardiac output from the right to the left side. We do evaluate both basic science and the clinical literature pointing to practical aspects of physiological knowledge.